Why Software Fails - We waste billions of dollars each year on entirel y preventable mistakes - Robert N., Charette (IEEE Spectrum, 2005)
We waste billions of dollars each year on entirely preventable mistake s. The biggest tragedy is that software failure is for the most part p redictable and avoidable. Unfortunately, most organizations don't see preventing failure as an urgent matter, even though that view risks ha rming the organization and maybe even destroying it. Understanding why this attitude persists is not just an academic exercise; it has treme ndous implications for business and society.